Empowerment through participation in community-based participatory research—effects of a physical activity promotion project among socially disadvantaged women - Röger-Offergeld, Ulrike; Kurfer, Eva; Brandl-Bredenbeck, Hans Peter (Frontiers in Public Health, 2023)
Introduction: Community-based participatory research (CBPR) approaches are associated with a range of positive impacts on empowerment. Only some studies investigate the influence of different modes of target group participation. The present study examines empowerment outcomes of women in difficult life situations through their participation as co-researchers in form of Photovoice in “Strong through Physical Activity” (German: Stark durch Bewegung), a CBPR project for physical activity (PA) promotion. The extent to which women's participation as co-researchers leads to empowerment is compared with other forms of participation. Methods: The Photovoice approach consisted of 3 components: 1) photo task, 2) focus group interviews, and 3) exhibition of photos. It was extended by participant observation. 18 women took part in Photovoice. They took photos, were involved in 4 focus groups, the analysis of the data, and supported their exhibition. Two further short focus group interviews took place at the end of the project, in which four more women participated. The interview guideline was based on the SHOWeD questions proposed within the framework of Photovoice, enriched with various other questions (e.g., self-efficacy, social contacts, and community involvement). The data were analyzed based on a grounded theory approach. Results: “Stark durch Bewegung” contributed to women’s empowerment in several ways. By participating in the project's PA programs, the women reported numerous empowerment effects, such as improved self-efficacy, perceived competencies like swimming and language skills, and social networks. By participating as co-researchers, they perceived a set of more generic competencies on organizational and community empowerment levels, that are comparable with other forms of participation (e.g., participation in a mixed cooperative planning group), but also differ from them at relevant points (e.g., encouraging them to reflect on their own PA behaviors). The willingness to get involved in Photovoice is estimated to be significantly higher than other possible forms of participation. Conclusion: Our findings support the notion that health promotion interventions with marginalized groups can contribute to their empowerment on multiple levels when participants become equal partners in the CBPR project. Including women as co-researchers to further empowerment outcomes and has advantages over other ways of participation.